Human dignity the constitutional value and the constitutional right - Barak, Aharon (Cambridge University Press, 2015)
"The concept of human dignity has a 2500 year history. As it moved through history, the concept was been influenced by different religions which held it as an important component of their theological approach. It was also influenced by the views of philosophers who developed human dignity in their contemplations. In the 20th century, the concept encountered a new phenomenon. The atrocities of the Second World War, and particularly the Holocaust of the Jewish people, brought human dignity into the forefront of legal discourse. As a result, constitutional and international legal texts began to adopt the concept, and jurists appeared alongside the theologians and the philosophers. Legal scholars were called upon to determine the theoretical basis of human dignity as a constitutional value and as a constitutional right. Judges were required to solve practical problems created by the constitutionalization of human dignity, as a value or as a right"-- Provided by publisher.